Who and how, DNA sensors in NETs-driven inflammation - Aubé, Félix-Antoine; Bidias, Amel; Pépin, Geneviève (Frontiers in Immunology, 2023)
During infections, neutrophil extracellular traps act like a meshwork of molecules that captures microbes. In contrast, during sterile inflammation the presence of NETs is usually associated with tissue damage and uncontrolled inflammation. In this context, DNA acts both as activator of NETs formation and immunogenic molecule fueling inflammation within the injured tissue microenvironment. Pattern recognition receptors that specifically bind to and get activated by DNA such as Toll-like receptor-9 (TLR9), cyclic GMP-AMP synthase (cGAS), Nod-like receptor protein 3 (NLRP3) and Absence in Melanoma-2 (AIM2) have been reported to play a role in NETs formation and detection. However, how these DNA sensors contribute to NETs-driven inflammation is not well understood. Whether these DNA sensors have unique roles or on the contrary they are mostly redundant is still elusive. In this review, we summarize the known contribution of the above DNA sensors to the formation and detection of NETs in the context of sterile inflammation. We also highlight scientific gaps needed to be addressed and propose future direction for therapeutic targets.